Exploring translanguaging and collaborative talk during group work in an entrepreneurship classroom at a TVET college - Jonkers, Jacqualine Rokeya (School of Education, 2025)
South African multilingual Technical and Vocational Education and Training (TVET) students encounter officially monolingual English environments in content-focused classrooms like entrepreneurship. However, in unofficial settings, they use their entire linguistic repertoire, switching and mixing their indigenous language with English during social interactions. They revert to using only English when communicating with teachers and engaging in reading and writing activities. This study explored translanguaging during collaborative group work by first-year multilingual students in an entrepreneurship classroom at a TVET college in the Western Cape. The study collected data from fifteen isiXhosa and Afrikaans speaking participants from the Western and Eastern Cape. All participants were enrolled in a National Accredited Technical Education Diploma (NATED) program within the Public Management department, exhibiting a wide range of English proficiency levels. Qualitative data was collected through classroom observations, video and audio recordings and group interviews. The study found that translanguaging is not only limited to social interaction but also used for pedagogical translanguaging. Translanguaging in social interaction expressed emotions, empathy and light-hearted humour. Whereas, pedagogical translanguaging through collaborative talk is demonstrated to be beneficial in promoting shared purpose and participation compared to disputational and cumulative talk. This type of talk demonstrated that it enhanced comprehension and participation by students actively exploring and challenging each other's ideas, offering disagreements and working together to make joint decisions by actively listening, asking questions and exchanging relevant information. Translanguaging is a common practice amongst multilingual students, so if it is fully exploited by TVET lecturers in the classroom they will be able to bridge the gap of their students' participation barriers due to language challenges.